Invariant metrics on lie groups : bi-invariance and one-parametre subgroups - Purho, Valto (2022)
We show that an admissible left-invariant geodetic metric on a connected Lie group is bi-invariant if and only if every one-parametre subgroup t 7→ exp(tX) is a geodesic.